PURWARUPA SISTEM PENDETEKSI LANGKAH DENGAN MENGGUNAKAN SENSOR ACCELEROMETER DAN GYROSCOPE BERBASIS ATMEGA32 - , MOHAMAD ARIF ZAKARIYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The navigation system is a method which is used to determine the position and direction of travel from the initial state. Currently, various studies appear to create a navigation system that applied in human by using some multiple sensors with high accuracy to obtain position, information and driving directions. In this case, it can be done by detecting the number of steps and distance by using Magnitude Threshold method . This step detection and distance, is an alternative from GPS to measure the distance traveled by people while they are in a room. A device that can detect and count the footsteps when people walk has been made on this research. This device runs by using ATMega32 as a data processing center, then ADXL345 accelerometer sensor and gyroscope sensor L3G4200D were used to detect the change of position, as well as a digital compass HMC5883L which was used to determine the direction of the Earth's magnetic field movement. For every transformation of position is detected, the data will be automatically updated then will be displayed on the Visual Basic 6.0 interface program. From the experiments that have been done, the accelerometer sensor can detect a footstep when the value of its magnitude is greater than 79 LSB with measurement error value 2.02 steps. While the detection step gyroscope is used to improve the detection of steps which was taken by the accelerometer.